Preparation of an aminographene–aliphatic hydroxyl-terminated polysiloxane hybrid for synergistic enhancement of the mechanical and tribological performance of monomer casting nylon 6. Issue 1 (21st October 2021) - Li, Chengjie; Guo, Minghui; Dai, Ying; Xu, Peikuan; Shi, Bin; Hou, Dewang; Li, Ruiguang
Abstract : UFG–AHPDMS hybrid with covalent linkage was prepared by reaction of GO/urea/AHPDMS. Addition of UFG–AHPDMS led to enhancement of mechanical/tribological property of MC PA6 with synergistic reinforcing/friction reduction effect. Abstract : A UFG–AHPDMS hybrid with covalent linkages was prepared by chemical grafting and reduction reaction of GO and urea, and then through reaction with AHPDMS using TDI as a bridge in CL melt. MC PA6/UFG–AHPDMS nanocomposites were synthesized via in situ polymerization from the stable colloidal suspension of UFG–AHPDMS/CL melt. AHPDMS molecules were confirmed to be grafted onto UFG layers through the aliphatic hydroxyl groups of AHPDMS and amino groups of UFG, and the UFG–AHPDMS hybrid exhibited better distribution in matrix with strong interfacial bonding and no phase separation occurring. In comparison with neat MC PA6, the introduction of UFG–AHPDMS resulted in a 20% and 24% increase in tensile strength and impact strength for the MC PA6/UFG–AHPDMS nanocomposite, higher than those of the MC PA6/UFG and MC PA6/AHPDMS composites, indicating the reinforcing and toughening effect of UFG–AHPDMS. Meanwhile, the friction coefficient and specific wear rate respectively decreased by more than 58% and 49% with a relatively smooth worn surface and narrower worn depth distribution, confirming the excellent synergistic friction reduction and anti-wear effect of UFG–AHPDMS on MC PA6. Moreover, a uniform and continuous UFG–AHPDMS hybrid tribofilm was formed by tribochemical reaction during the friction process, and was responsible for the reduction of the friction coefficient and wear rate.